2016
DOI: 10.1152/advan.00081.2015
|View full text |Cite
|
Sign up to set email alerts
|

Visual event-related potential studies supporting the validity of VARK learning styles' visual and read/write learners

Abstract: The validity of learning styles needs supports of additional objective evidence. The identification of learning styles using subjective evidence from VARK questionnaires (where V is visual, A is auditory, R is read/write, and K is kinesthetic) combined with objective evidence from visual event-related potential (vERP) studies has never been investigated. It is questionable whether picture superiority effects exist in V learners and R learners. Thus, the present study aimed to investigate whether vERP could sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
0
22
1
4
Order By: Relevance
“…Additionally, recent published data have demonstrated patients with advanced kidney disease may have challenges in understanding learning material and practitioners should tailor education according to the needs of the patients 14. Learning style refers to the preference and effectiveness of the mode of instruction for each individual 15–17. Therefore, accommodating to individual learning styles may impact on long-term retention of knowledge, which may in turn reduce adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent published data have demonstrated patients with advanced kidney disease may have challenges in understanding learning material and practitioners should tailor education according to the needs of the patients 14. Learning style refers to the preference and effectiveness of the mode of instruction for each individual 15–17. Therefore, accommodating to individual learning styles may impact on long-term retention of knowledge, which may in turn reduce adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…P200 is considered as one of the most important components in the recognition process. It is associated with basic sensory processes, such as searching for complex visual stimuli and detecting target stimuli and appears when a subject recognizes words shown on a computer screen [24]. This may reflect the process of comparing visual input with the stored knowledge or generated expectations.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,22 However right handers being auditory learners in our cohort goes against many studies where they are found to be visual learners and kinesthetic learners. 4,22,23 From primary education all the students are trained to listen and learn facts through talks which is the traditional approach to teaching; primarily in India, and hence the cause for the prominent auditory preference in India. Previously, studies have shown learners with ambidexterity performed the worse in nearly all measures of development.…”
Section: Discussionmentioning
confidence: 99%